Role of life-cycle externalities in the valuation of protic ionic liquids – a case study in biomass pretreatment solvents - Baaqel,H; Díaz,I; Tulus,V; Chachuat,B; Guillén-Gosálbez,G; Hallett,JP (Green Chemistry, 2020)
Ionic liquids have found their way into many applications where they show a high potential to replace traditional chemicals. But there are concerns over their ecological impacts (toxicity and biodegradability) and high cost, which have limited their use so far. The outcome of existing techno-economic and life-cycle assessments comparing ionic liquids with existing solvents has proven hard to interpret due to the many metrics used and trade-offs between them. For the first time, this paper couples the concept of monetization with detailed process simulation and life-cycle assessment to estimate the true cost of ionic liquids. A comparative case study on four solvents used in lignocellulosic biomass pretreatment is conducted: triethylammonium hydrogen sulfate [TEA][HSO4], 1-methylimidazolium hydrogen sulfate [HMIM][HSO4], acetone from fossil sources, and glycerol from renewable sources. The results show that the total monetized cost of production accounting for externalities can be more than double the direct costs estimated using conventional economic assessment methods. The ionic liquid [TEA][HSO4] is found to have the lowest total cost, while the renewable solvent glycerol presents the highest total cost. We expect this methodology to provide a starting point for future research and development in sustainable ionic liquids